Electronic Contracts (E-Contracts) and Validity in Indonesian Civil Law: Analysis of Article 1320 of The Civil Code and The ITE Law - Hery Dwi Utomo; Bulelani Thukuse (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The development of information technology has given rise to a new form of business transaction: the electronic contract. This contract form replaces the traditional process that requires a physical meeting between the parties. However, questions arise regarding the validity of e-contracts from the perspective of Indonesian civil law, specifically based on Article 1320 of the Indonesian Civil Code (KUHPerdata) and the provisions of Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE). This research aims to analyze the validity of electronic contracts as legally binding agreements and to assess the extent to which the ITE Law can serve as their legal basis. Using a normative juridical legal research method, the research results show that e-contracts are valid and binding as long as they meet the requirements for the validity of an agreement under Article 1320 of the Civil Code, namely consent, capacity, a specific object, and a lawful cause. The ITE Law expands the recognition of electronic evidence and digital signatures as valid evidence in civil law. Thus, electronic contracts have the same legal force as conventional contracts, as long as they meet the principles of free will and the integrity of a reliable electronic system.